Digitalization of Tourism Villages: Digital Marketing Strategies for the Development of Pematang Johar Tourism - Hana Salsabila Lubis; Putri Mentari; Sipnarong Kanchanawongpaisan; Muhammad Hafiz Abd.Rashid; Nurul Ilyana Binti Muhd Adnan; Chyntia Agustin (Eastasouth Journal of Effective Community Services, 2025)
Digital transformation is increasingly crucial for tourism villages in Indonesia as tourist behavior shifts toward digital technology for travel decisions. However, many villages remain behind in digital literacy and online marketing skills. Pematang Johar Tourism Village in Deli Serdang Regency, North Sumatra, exemplifies this challenge. Despite its strong agricultural and cultural potential, it struggles to promote itself effectively due to limited human resources, inadequate infrastructure, and minimal understanding of digital marketing strategies. To address these gaps, a community service program emphasizing digitalization training and mentoring was implemented. The program focused on improving digital literacy, developing creative promotional content, and utilizing social media as a marketing tool. Through participatory and hands-on learning, participants enhanced their ability to create engaging digital content, manage social media platforms, and highlight local cultural values in promotions. The #ExplorePematangJohar campaign further boosted the village’s online visibility and digital identity.